Self-medication among health care workers in a tertiary hospital in Southern Nigeria: knowledge, attitude, and practices (Medical Journal of Indonesia, 2020)
BACKGROUND Self-medication is linked to the inappropriate and irrational use of medicines. This study aimed to determine the knowledge, attitude, and practice of self-medication among health care workers (HCWs) in a tertiary hospital in Southern Nigeria. METHODS In a cross-sectional study carried out between June 2018 and December 2018 at Irrua Specialist Teaching Hospital, Edo State, 206 consenting HCWs were interviewed using validated questionnaires on their knowledge (assessed as good, fair, and poor), attitude (positive and negative), and practice of self-medication. Data analysis was performed using SPSS version 21 (IBM Corp., USA). Bivariate analysis was carried out using chi-square. Statistical significance was set as p<0.05. RESULTS Prevalence of self-medication in the last 4 months was 89.3%, and significantly decreased with increasing age (p = 0.04) and holding a positive attitude toward self-medication (p<0.01). Knowledge of self-medication was fair for the majority 111 (53.9%). Most of the medications were used for headache (92.4%), fever (81.5%), diarrhea (75.0%), and respiratory infections (61.4%). Common drugs self-medicated included antimalarials (91.3%), analgesics (81.0%), and antibiotics (71.2%). 39 subjects (21.2%) self-medicated with tranquilizers. Familiarity with the treatment options was the main reason for self-medication for 60.9% of the respondents. CONCLUSIONS Self-medication was prevalent among HCWs in the study area. Concerted efforts are needed to educate HCWs on responsible self-medication. On a broader scale, restrictions should be enforced on the sale of prescription drugs, such as antibiotics and sleeping pills, and drug dispensers should provide effective counseling before dispensing.